Ultrasonic wave propagation in non homogeneous media - Léger, A. (Springer, 2017)
Non Destructive Testing and Non Destructive Evaluation using Ultrasounds covers an important field of applications and requires a wide range of fundamental theoretical, numerical and experimental investigations. In the present volume, the reader will find some relevant research results on wave propagation in complex materials and structures which are concerned with today's problems on composites, bonding, guided waves, contact or damage, imaging and structural noise. The fifth meeting of the Anglo-French Research Group on "Wave propagation in non homogeneous media with a view to Non Destructive Testing", where all these results were presented, was held in Anglet, France, June 2-6, 2008.